Investigating the Impact of Market Openness on Economic Growth for Poland: An Autoregressive Distributed Lag Bounds Testing Approach to Cointegration - Dritsaki, Chaido; Stamatiou, Pavlos (International Journal of Economics and Financial Issues, 2019)
The aim of this paper is to analyze the relationship between international trade, economic and financial development for Poland during the period 1990-2016. For the analysis of this relationship we apply the autoregressive distributed lag (ARDL) technique and the error correction model (ECM) as it was formed by Pesaran and Shin (1999) and Pesaran et al. (2001), as well as the augmented Cobb-Douglas production function formed by Mankiw et al. (1992). The results of ARDL test and ECM confirm the existence of long and short run equilibrium relationship among variables of the examined model. Capital seems to be a driver of economic growth both in the short and long run, while labor has a negative impact in Poland's economic growth. However, trade openness and financial development found to be insignificant on economic development both in the short and long run. Keywords: Cobb-Douglas production function, ARDL bounds test, Vector Error Correction Model JEL Classifications: F43, C52, C23, 047 DOI: https://doi.org/10.32479/ijefi.8327